DETERMINAN MINAT PESERTA DIDIK DALAM MEMILIH PRODI DI PERGURUAN TINGGI DIMASA PANDEMI - Windari, Windari; Lestari, Sry (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
The purpose of this study was to determine the determinants of student interest in choosing the Islamic Banking Study Program at IAIN Padangsidimpuan, because of the interest in entering higher education, there was a decrease in the number of students during this pandemic by up to 30%. This research method is a descriptive qualitative method, namely to find determinants of student interest in choosing Islamic banking study programs. The sample of this research is 97 high school students (SMA/SMK) and (MAN/Pesantren), descriptive statistical analysis technique in the form of cross tabulation, graph, average and frequency. The results of this study can be seen from internal factors and external factors from the dimensions of 3 aspects, namely aspects of knowledge, religiosity, and environment. The internal factor of high school and vocational students' interest in choosing the Islamic Banking Study Program at IAIN Padangsidimpuan during the pandemic, was in the low category at 79.38%, and the medium category at 20.62%. Meanwhile, the interest of Islamic Boarding School and MAN students is in the medium category by 94.80%, and the low category by 5.20%. External factors, the interest of high school and vocational high school students in choosing the Islamic Banking Study Program at IAIN Padangsidimpuan during the pandemic, was in the medium category at 77.31%, and the low category at 20.69%. Meanwhile, the interest of Islamic Boarding School and MAN students is in the low category by 5.20%, and the medium category by 94.80%.